Desenvolvimento da estação labens usando sensor SPN1 - Jacobs, Rafael Solheid (2025)
Measuring solar radiation on Earth is crucial for understanding climatic and atmospheric influences and for developing solar energy projects. This enables the efficient installation of photovoltaic systems in different regions, maximizing the capture of solar energy throughout the year. Some solarimetric stations, such as those of the Solar Energy Research Stations Network (EPESOL) at UTFPR in Curitiba, collect information on direct, diffuse, and global radiation, along with meteorological data. These stations use instruments like pyranometers to measure solar irradiance, which is essential for various applications, including weather forecasting and the efficiency of solar energy systems. A lower-cost sensor with no moving parts: the SPN1, was introduced into the EPE Standard Station. Although accurate in measuring global solar radiation, the SPN1 sensor presents lower precision in measuring diffuse solar radiation, requiring adjustments and corrections. It can be used in meteorological stations and environmental monitoring systems. The objective of this work is to install, reprogram the datalogger with the new sensor’s functions, and compare the SPN1 sensor with the already existing CMP10, used in the SONDA station, for the validation of solar irradiance data. Sky conditions with scattered clouds caused peaks in direct radiation on the SPN1 sensors, while the SONDA system smooths these effects due to tracking and angular limitation. The SPN1 may saturate or exhibit non-linearities that increase the overestimation of DNI when solar irradiance is very intense, which occurs in the months closer to summer. The April measurements from the SPN1 sensor compared to the CMP10 sensor showed varied results. Diffuse irradiation and global horizontal irradiation showed variations of -3.1% and -1.6%, respectively, while direct irradiance had a variation of 11.3%. Although the accuracy of the SPN1 was surpassed in some cases, the observed variations are considered acceptable for the sensor’s use. In summary, the results confirm that the SPN1 sensor is a viable alternative for solar irradiation measurements, provided that its inherent limitations, such as the tendency to overestimate DNI under high irradiation conditions, are considered, offering a relevant contribution to energy monitoring.